Studying the pharmacokinetics of biotechnological medicinal products on the example of monoclonal antibodies - V. V. Smirnov; O. A. Petukhova; A. V. Filatov; D. A. Kudlay; M. R. Khaitov (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Therapeutic monoclonal antibodies (mAbs), which are developed to treat many pathologies, including cancer, autoimmune and infectious diseases, are one of the fastest growing classes of medicinal products. Given the large number of mAbs in the pipeline and continued interest from pharmaceutical companies, the mAb market is expected to continue to grow in the coming years. To maximise both the therapeutic benefit and the safety of medicinal products in this class, it is essential that their pharmacological properties be carefully characterised and understood.The aim of the study was to analyse literature data on approaches to studying the pharmacokinetics of mAbs. This review presents data on the main physicochemical and pharmacological properties of mAbs and compares them with small molecules. The article describes the influence of various factors on mAb pharmacokinetics.For example, such factors include the method of administration, hydrophilicity, and charge of the mAb, individual characteristics of the patient (body weight, plasma albumin levels, genetic characteristics, etc.), and concurrent administration of other medicinal products. The authors evaluated the role of intra- and inter-individual variability of pharmacokinetic parameters. The rapid development of this group of medicinal products and the emergence of new promising molecules are indicative of the need to study the pharmacokinetics and pharmacodynamics of mAbs in detail and to maximise both the therapeutic benefit and the safety of the medicinal products in this class.